2021
DOI: 10.1111/jog.14654
|View full text |Cite
|
Sign up to set email alerts
|

Application of serum markers in diagnosis and staging of ovarian endometriosis

Abstract: Aims Laparoscopic surgery is widely used for diagnosing ovarian endometriosis but it has medical risks. This study explored the application of blood indicators in diagnosis and staging of ovarian endometriosis, aiming to develop a noninvasive diagnostic method. Methods A total of 190 ovarian endometriosis patients were included in observation group, among these participants, 77 patients among them were stages I–II, and the rest 113 patients were stages III–IV, and a total of 103 healthy women as control group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
(33 reference statements)
0
8
0
1
Order By: Relevance
“…After screening, a total of 15 studies were finally included [ 11 24 ]. All the included studies were diagnostic tests, including 2262 patients with ovarian cancer, all confirmed by national pathological standards, and the control group included 2300 patients with benign ovarian disease and healthy people, and a total of 4562 cases were included.…”
Section: Resultsmentioning
confidence: 99%
“…After screening, a total of 15 studies were finally included [ 11 24 ]. All the included studies were diagnostic tests, including 2262 patients with ovarian cancer, all confirmed by national pathological standards, and the control group included 2300 patients with benign ovarian disease and healthy people, and a total of 4562 cases were included.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that VEGF, MMP-2 and MMP-9 are significantly elevated in the serum of patients with endometriosis ( 62 ). In contrast, CA-125 and CA-199 are significantly increased in the serum of patients with endometriosis and together with some other serological indicators can be used as a reference for the early diagnosis and staging of endometriosis ( 63 , 64 ). Some study found that Gal-3 was over-expressed in all forms of endometriosis ( 65 ), it played an important role in the development of endometriosis and might be a target for endometriosis treatment ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of AFP have also been found to be altered in some ovarian lesions. Ting Tang et al [22] observed that the serum levels of AFP in 190 patients with ovarian endometriosis were obviously downward in comparison with 103 healthy subjects. Morever, the value of AFP, CA125, CA199, and HE4 can be combined to distinguish the two groups, with high sensitivity and specificity [22].…”
Section: Introductionmentioning
confidence: 99%
“…Ting Tang et al [22] observed that the serum levels of AFP in 190 patients with ovarian endometriosis were obviously downward in comparison with 103 healthy subjects. Morever, the value of AFP, CA125, CA199, and HE4 can be combined to distinguish the two groups, with high sensitivity and specificity [22]. A literature review revealed that serum AFP increased in ovarian sertoli-leydig cell tumors [23].…”
Section: Introductionmentioning
confidence: 99%